HUBUNGAN KEBIASAAN SARAPAN DENGAN PRESTASI BELAJAR SISWA SEKOLAH DASAR NEGERI 13 KABILA KECAMATAN KABILA KABUPATEN BONE BOLANGO - Anasiru, M. Anas; Misnati, Misnati; Puspawati, Ni Nengah (JOURNAL HEALTH AND NUTRITIONS, 2017)
ABSTRACT Learning achievement is the mastery of knowledge or skills developed through the subjects, embodied in the form of values or numbers. Learning achievement that is displayed with the scores or numbers created by teachers based on assessment guidelines on each student is different, based on the level of mastery of the competencies that have been set. The problem studied is whether breakfast has an influence on student achievement in school. This study aims to determine the relationship between Breakfast Habits and Student Achievement in State Elementary School Number 13 Kabila District of Kabila Bone Bolango Regency. The research method is analytic survey with cross-sectional survey design. The population is 102 students enrolled in SDN 13 Kabila.Samples are taken from class III, IV and V, using simple random sampling. Independent variable is breakfast habit and the dependent variable is student achievement in school. Data collection is done by using questionnaire.Data analysis method is "Chi-Square (X2)." The result of statistic test obtained by the researcher found that X2 count was bigger than X2 table (10,935> 9,488). Where Ha is accepted and Ho is rejected. Conclusion: there is Relationship between Breakfast Habit and Student Achievement at State Elementary School 13 Kabila Sub District Kabila of Bone Bolango Regency. Keywords: Breakfast Habit, Learning Achievement, Student ABSTRAK Prestasi belajar adalah penguasaan pengetahuan atau keterampilan yang dikembangkan melalui mata pelajaran, diwujudkan dalam bentuk nilai atau angka. Prestasi belajar yang ditampilkan dengan nilai atau angka dibuat guru berdasarkan pedoman penilaian pada masing-masing siswa berbeda, berdasarkan tingkat penguasaan kompetensi yang telah ditetapkan. Permasalahan yang dikaji adalah apakah sarapan memiliki pengaruh dengan prestasi belajar siswa di sekolah. Penelitian ini bertujuan untuk mengetahui Hubungan Kebiasaan Sarapan Dengan Prestasi Belajar Siswa Sekolah Dasar Negeri 13 Kabila Kecamatan Kabila Kabupaten Bone Bolango. Metode penelitian yang digunakan survei analitik dengan rancangan survey cross sectional. Populasi sebanyak 102 siswa yang terdaftar di SDN 13 Kabila sampel yang diambil dari kelas III, IV dan V, menggunakan simple random sampling. Variabel bebas yaitu kebiasaan sarapan dan variabel terikat yaitu prestasi belajar siswa di sekolah Pengumpulan data dilakukan dengan menggunakan kuesioner, analisis data menggunakan “ Chi Square (X2).” Hasil uji statistik yang diperoleh peneliti didapatkan bahwa X2 hitung ternyata lebih besar dari X2 tabel ( 10,935 > 9,488). Dimana Ha diterima dan Ho ditolak. Kesimpulan penelitian ini adalah terdapat Hubungan Kebiasaan Sarapan dengan Prestasi Belajar Siswa Di Sekolah Dasar Negeri 13 Kabila Kecamatan Kabila Kabupaten Bone Bolango Kata Kunci: Kebiasaan Sarapan, Prestasi Belajar, Siswa